The determinants of consumer purchasing intention towards consuming imported food products through e-commerce platform in Malaysia - Khaw, Carmen Jia Wen; Lee, Si Min; Loke, Hao Ying; Low, Kah Xian; See, Zi Ying (2022)
Since 2019, the spreading of the COVID-19 pandemic had a huge impact globally. The Malaysian Government had decided to implement Movement Control Order (MCO) by imposing regulations to limit people’s movement, due to the tremendous increase in active cases in Malaysia. Ever since then, the use of e-commerce platforms has started to become more popular due to the significant change in people’s lifestyles. Even though before the occurrence of the COVID-19 pandemic, purchasing through e-commerce platforms had slowly become a trend, the usage of e-commerce was being stressed particularly throughout this pandemic period. People intend to purchase more products including electrical products, home appliances, necessary products, and others. Yet regarding the necessary products, people even utilize the convenience of the e-commerce platform by purchasing fresh food, dry food, and also imported food. Hence, this study aims to understand whether perceived quality, perceived risk, price, brand image, and ease of use of e-commerce platforms towards consumers’ purchasing intention to consume imported food products through e-commerce platforms. To carry out more understanding on the determinants that motivate consumers’ purchasing intention. Thus, this study brings in the Cognitive Evaluation Theory (CET) to investigate what motivates consumers’ behaviour to trigger their purchasing intention. In addition, to understand more about whether the difficulty of the usage of the technology affects purchasing intention, this study also brings in the Technology Acceptance Model (TAM). Besides, this research will be based in Malaysia, with a sample size of 384 respondents. The research data were generated from questionnaires and were analysed by the Statistical Package for the Social Sciences (SPSS). Pearson correlation coefficient analysis and multiple regression are applied as a way to identify the relationship among variables. Last but not least, this research study will enable researchers and e-commerce sellers to improve in the aspect of e-commerce platforms as well as to fulfil consumers’ expectations toward imported food products in future.